STUDI IN SILICO SENYAWA AKTIF DARI JAHE (Zingiber officinale) DAN KERSEN (Muntingia calabura L.) SEBAGAI INHIBITOR MAIN PROTEASE (Mpro) DARI SARS-CoV-2 - Tahir, Masdiana; Maryam, St. (Fakultas Farmasi UMI, 2024)
Coronavirus disease is an infectious disease caused by the SARS-CoV-2 coronavirus, which is an RNA virus consisting of four structural proteins and sixteen non-structural proteins responsible for viral multiplication. One of the proteins is the main protease (Mpro). Inhibition of Mpro is potentially effective as a COVID-19 drug because it will cause the loss of the virus's replication and transcription abilities, so that the virus is unable to survive. The purpose of this study is to determine what chemical compounds in ginger (Zingiber officinale) and kersen (Muntigia calabura) plants have the potential as COVID-19 drugs with the Mpro inhibition mechanism. This research method is in silico using molecular docking method with PyRX software. The results showed that of the 70 chemical compounds from ginger (Zingiber officinale), there are 3 compounds that have potential because they have better activity than the N3 inhibitor comparison ΔG -8.0 kcal/mol, namely Zingiberoside B (-8.6 kcal/mol), Zingiberoside C (-8.5 kcal/mol) and Shogasulfonic acid D (-8.2 kcal/mol). Meanwhile, of the 10 chemical compounds from Jamaica cherry (Muntigia calabura), there are 4 chemical compounds that have potential as Mpro SARS-CoV-2 inhibitors, namely Kempferol 7-(6''-p-coumarylglucoside) or Biondnoid A (-9. 1 kcal/mol), Hiravanone (-8.4 kcal/mol), 5,7,3',4' - Tetrahydroxy - 6, 8 - di - C -prenylflavanone (-8.4 kcal/mol), and Myrtillin (-8.3 kcal/mol).